IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH FLASH CARDS - Kumaat, Swita Wulan; Tuna, Jim Ronny; Maru, Mister Gidion (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study focuses on improving students’ vocabulary mastery and whether it can improve through flash cards. The purpose of this study was to find out whether the learning method using picture media in the form of flashcards improved student’s vocabulary mastery at SMP Negeri 5 Tondano. In this study, the researcher used quantitative approach with a pre-experimental design with one group pre-test and post-test. Students take the pre-test (T1) prior to treatment, and post-test (T2) is administered following treatment. The subject of this study was seventh grade students with a total of 11 children as participants. The results of this study shown that mean score of the post-test (93,72) was higher than mean score pre-test (69,81). The results correlate with several previous studies. It means that the outcomes of this study provide relevance to the theory of previous studies that flashcards encourage students' vocabulary learning. It can be concluded that the used of flashcard as a learning media is effective to improve student’s vocabulary mastery.